UPAYA MENINGKATKAN KEAKTIFAN BELAJAR MATEMATIKA PADA MATERI TURUNAN FUNGSI TRIGONOMETRI MELALUI MODEL PEMBELAJARAN COOPERATIVE NUMBER HEAD TOGETHER (NHT) PESERTA DIDIK KELAS XII MIPA 2 SMA NEGERI 1 MUTIARA - Fazillah Fazillah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2022)
The purpose of this study was to determine the effect of applying the Number Head Together type of cooperative learning model in learning mathematics on learning activities and learning outcomes of Class XII MIPA 2 SMA Negeri 1 Mutiara students on trigonometric function derivatives. This research uses classroom action research as much as two cycles. Each cycle consists of four stages, namely planning (planning), implementation (acting), observation (observing) and reflection (reflecting). From the results of data analysis, it was found that the learning activity and learning achievement of students increased from cycle I to cycle II, namely the first cycle obtained an average student activity of 2.50 which was categorized as less good,and in the second cycle the average student activity was obtained 3 ,41 which is categorized as good. Meanwhile, the learning outcomes of students also increased, namely in the first cycle, 76.67% of students were completed and in the second cycle, 93.33% were obtained who completed or reached the KKM (≥70). Thus, the selection of the Number Head Together type of learning model in learning mathematics can increase student learning activity and student learning outcomes for Class XII MIPA 2 SMA Negeri 1 Mutiara on Derivative material.Keywords: active learning mathematics, learning outcomes of mathematics, derived material, learning model type Number Head Together.